OEA loaded liposomes with the neuroprotective effect for stroke therapy - Wu, Shichao; Yang, Xiangrui (Frontiers in Chemistry, 2022)
With high mortality, stroke has become a serious threat to human health. Nevertheless, the strategy for stroke therapy is quite limited in the clinic till now. In this research, we prepared a novel neuroprotective nanoformulation (OEA Liposomes) via encapsulating endogenous N-oleoylethanolamine (OEA) in liposomes for intravenous administration. The formulation largely increased the solubility and bioavailability of OEA. Then the following systematic experiments stated the excellent neuroprotective effect of OEA Liposomes in vivo. The survival rate of the nanodrug group was largely increased to 75%, while that of the Middle Cerebral Artery Occlusion (MCAO) group was only 41.7%. And the severe neurological functional deficit of the MCAO rats was also significantly improved. What’s more, the OEA Liposomes could inhibit the apoptosis of neurons and the inflammation of reperfusion to a very slight level, indicating their outstanding neuroprotective effect. These results indicated that the OEA Liposomes have a great potential for clinic anti-stroke application.